Workplace Bullying in Education - Καλλιατάκη, Ελένη; Γεράκη, Ακριβούλα (Education Sciences, 2022)
Bullying is a global phenomenon that is being investigated. But especially among the educators such phenomena have no place. The lack of quality research on the issue of workplace bullying in primary education has prompted the interest of researchers. The technique of semi-structured interviews was chosen. The sample consisted of twenty (20) teachers from different schools of N. Heraklion, Crete. The results showed that "workplace bullying" and "victimization" existed. The teachers identified them as psychological in nature, which manifest in different forms. Also, their definitions were given.Specific factors affect their manifestation such as working conditions, etc., while "gender" does not seem to affect to a large extent, such as age and educational level. The consequences of work bullying mainly concern psychosomatic illnesses. Consequences are observed in personal, professional life but mainly in the educational organization. The role of management is as important as the immediate "clearing of accounts", the existence of "friendly" relations, the communication of the phenomenon and the psychological support if needed.